Fabrication and Processing of Shape Memory Alloys - Mehta, Kush; Gupta, Kapil (Manufacturing and Surface Engineering,, 2019)
This book showcases different processes of fabrication and processing applied to shape memory alloys. It provides details and collective information on working principles, process mechanisms, salient features, novel aspects, process capabilities, properties of material and unique applications of shape memory alloys. The recent progress on fabrication and processing are specially addressed in this book. It covers major topics of manufacturing such as machining, joining, welding and processing of shape memory alloys. .